Vulnerability evaluation of scoured bridges under floods. (1st February 2017) - Hung, Chung-Chan; Yau, Wen-Gi
Highlights: The effects of scour on the behavior of bridges under floods are examined. Retrofitting approaches on lessening bridge vulnerability are evaluated. A rational method is proposed for vulnerability assessment of scoured bridges. The proposed method can identify the vulnerability of scoured bridges. Abstract: The erosion or removal of soil from around bridge foundations due to scour can significantly increase the vulnerability of bridges under flood conditions. It has been reported that scour at bridge foundations due to flooding is a major cause of bridge failure. While retrofitting bridge foundations with additional piles is a common approach to improve the resilience of scour-critical pile-supported bridges, its effectiveness remains to be explored. The objective of the study is to develop a rational vulnerability evaluation method for scoured pile-supported bridges under flood conditions. In addition, the effects of scour depths and foundation retrofitting work on the failure mechanism and vulnerability of bridges subjected to flood-induced loading are quantitatively investigated. The investigation is conducted using a complex nonlinear three-dimensional finite element model that accounts for the interactions between bridge structures, soils, water flow, and pile foundations. The validity of the developed vulnerability evaluation method is demonstrated using the Shuang-Yuan Bridge that collapsed during a flood event in 2009. Finally, a safety management procedure for scour-critical bridges is suggested.